An Ethical Framework for Environmental Sustainability: Reestablishing Deep Ecology through Richard Powers’ The Overstory - Prabha, S.; Rathna, P. (Studia Ecologiae et Bioethicae, 2025)
The exploitation of the Earth’s precious resources has accelerated to a level that is causing irreversible environmental damage, including natural disasters and health hazards. However, most of the natural calamities we face today result from man’s anthropocentric attitude. The modern world lacks sufficient ethical values to preserve the environment. As a result, humanity faces a severe environmental crisis in which the survival of all living beings is at risk. It has therefore become essential to restore lost human values so that people can live harmoniously on Earth, protecting its natural balance and refraining from harming the environment for personal gain. Recognizing that a healthy living environment depends on valuing and respecting nature for its own sake is crucial. This paper examines how Richard Powers’ Pulitzer Prize-winning novel, The Overstory, reinterprets Deep Ecology to promote a healthy ecosystem and sustainability by addressing the challenges we face today. The study establishes an ethical framework for understanding the interdependence of human and non-human life by connecting individual stories with those of trees.